A Sanctioning the Violation of the Right to Free Access to Public Information and its Character in a Tool in the Fight Against Corruption - Slamkov, Gjorgi (International Scientific Journal Vision, 2017)
Free access to public information is an important tool on the way to achieving full transparency and openness of institutions towards citizens, that is, it is a strong tool in the fight against corruption.This right allows citizens to become more familiar with the work of the institutions and, on this basis, without intermediaries, to participate in the public affairs and decision-making process in a real and responsible manner.The right to free access to information held by the institutions strengthens the principle of responsibility in the work of all holders of power and creates conditions for quality construction and stability of the system of a democratic society. This right has contributed to the effective fight against corruption. Namely, corruption is based on secrecy, the institutions become corrupt when the public has no insight into their work. In this sense, the more the work of public institutions is offered to the public, the chance that they are corrupt will be less.The protection and practical realization of the right to free access to public information impose the need for effective legal instruments to sanction the violation of the law.